On the wake of an isolated rotating wheel: An experimental and numerical investigation. Issue 227 (August 2022) - Patel, Dipesh; Garmory, Andrew; Passmore, Martin
Abstract: The wake of an isolated, rotating wheel of a geometry typical of those used in open-wheel motorsport, is investigated. The CFD is validated by comparing the wake data gathered from this method with the data from the PIV wind tunnel experiments, where analysis of the data showed a good agreement between the two methods. A comparison of the mean and instantaneous flow-fields obtained from the CFD shows significant differences in the wake topology. The time-averaged illustration of the flow shows an inverted "T" shape, and consists of a pair of upper and lower counter-rotating vortices that merge downstream, with the upper being dominant. The instantaneous wake follows the same fundamental shape, but consists of incoherent macro-scale eddies, together with these counter-rotating vortices in a deformed state. Analysis of the unsteadiness of the wake via proper orthogonal decomposition reveals significant transverse and vertical velocity fluctuations. The transverse velocity fluctuations are driven by both the contraction and expansion of the contact patch wake and the instability of the merged counter-rotating vortex pair that eventually lead to a transverse flapping motion of the bulk wake. The instability of these vortices also leads to vertical velocity fluctuations in the vortex-induced downwash region.